A Validated RP – HPLC Method for Simultaneous Estimation of Cefixime and Cloxacillin in Tablets. Issue 3 (2008) - Rathinavel, G.; Mukherjee, P. B.; Valarmathy, J.; Samueljoshua, L.; Ganesh, M.; Sivakumar, T.; Saravanan, T.
Abstract : This paper presents a RP-HPLC method for the simultaneous estimation of cefixime and cloxacillin in tablets. The process was carried out on C18 column (5 μm, 25 cm × 4.6 mm, i.d) using phosphate buffer (pH 5.0), acetonitrile and methanol in the ratio 80:17:3 respectively as a mobile phase at a flow rate of 2mL/min. Wavelength was fixed at 225 nm. The retention time of cefixime and cloxacillin was found to be 5.657 and 6.200 min, respectively. The developed method is rapid and sensitive and it can be used for estimation of combination of these drugs in tablets.